If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3)(4)=(2x+8)(4x-3)
We move all terms to the left:
(3)(4)-((2x+8)(4x-3))=0
We multiply parentheses ..
-((+8x^2-6x+32x-24))+34=0
We calculate terms in parentheses: -((+8x^2-6x+32x-24)), so:We get rid of parentheses
(+8x^2-6x+32x-24)
We get rid of parentheses
8x^2-6x+32x-24
We add all the numbers together, and all the variables
8x^2+26x-24
Back to the equation:
-(8x^2+26x-24)
-8x^2-26x+24+34=0
We add all the numbers together, and all the variables
-8x^2-26x+58=0
a = -8; b = -26; c = +58;
Δ = b2-4ac
Δ = -262-4·(-8)·58
Δ = 2532
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{2532}=\sqrt{4*633}=\sqrt{4}*\sqrt{633}=2\sqrt{633}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-26)-2\sqrt{633}}{2*-8}=\frac{26-2\sqrt{633}}{-16} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-26)+2\sqrt{633}}{2*-8}=\frac{26+2\sqrt{633}}{-16} $
| -5/3+1/2u=-4/5 | | 5-7+8x=-7x-2 | | 3m+14=4√49+(7*4) | | 365-18-d=185 | | y=-2.5(3.5)+18 | | 11+x/4=10 | | 9+3n=32 | | -7y+9=40 | | 6+10x=9x-3 | | 37=9u | | 2=–3t+8 | | (a/16)+(-24)=-19 | | 3x+27=×+11 | | 5y^2+19y-12=0 | | w+12=-10 | | 5^(2x+3)=1/625 | | -(n+12)=-4n-10+3n+2 | | -8+10x=6x+44 | | (-4v/10)=22 | | 72.50=2.9c | | -6y+14=4y+32 | | -5x-16=18x-3 | | -7x+3=10-6x | | 1/2-5/8x=7/8x=7/2 | | x.x-8=13 | | c−2.44=2.56 | | X/7=y/14+1/2 | | -t+9=5+-9 | | 32x+5x=136 | | 3(4y+7-6y)=5(2y-2)-1 | | k-11/4=-7 | | 4x+8+8x=4x(x+2) |